2021
DOI: 10.1177/19322968211026978
|View full text |Cite
|
Sign up to set email alerts
|

A Glucose-Only Model to Extract Physiological Information from Postprandial Glucose Profiles in Subjects with Normal Glucose Tolerance

Abstract: Background: Current mathematical models of postprandial glucose metabolism in people with normal and impaired glucose tolerance rely on insulin measurements and are therefore not applicable in clinical practice. This research aims to develop a model that only requires glucose data for parameter estimation while also providing useful information on insulin sensitivity, insulin dynamics and the meal-related glucose appearance (GA). Methods: The proposed glucose-only model (GOM) is based on the oral minimal model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…However, the use of PPG measured from blood taken between 3 and 7.9 h is inferior to PPG 4-7.9h , as PPG measured from blood taken between 3 and 3.9 h did not return to the baseline level and it was higher than PPG 4-7.9h [10]. In addition, PPG returned to baseline four hours after a meal regardless of meal type and mealtime [11]. Moreover, the current study confirmed that hourly PPG 4-7.9h was similar across the duration from 4 to 7.9 h. Therefore, it is necessary to investigate the association between PPG 4-7.9h and CVD mortality.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…However, the use of PPG measured from blood taken between 3 and 7.9 h is inferior to PPG 4-7.9h , as PPG measured from blood taken between 3 and 3.9 h did not return to the baseline level and it was higher than PPG 4-7.9h [10]. In addition, PPG returned to baseline four hours after a meal regardless of meal type and mealtime [11]. Moreover, the current study confirmed that hourly PPG 4-7.9h was similar across the duration from 4 to 7.9 h. Therefore, it is necessary to investigate the association between PPG 4-7.9h and CVD mortality.…”
Section: Discussionmentioning
confidence: 92%
“…However, those studies did not investigate CVD mortality. In addition, measuring glucose at 1 or 2 h after a meal may not be ideal, as variation in diet could change PPG by more than 20 mg/dL [11], and variation in blood collection time (±0.5 h in practice [40]) could introduce bias as PPG is time sensitive around 1 to 2 h [11]. In contrast, the current study showed that PPG 4-7.9h was stable and hourly PPG 4-7.9h was comparable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 That study has some limitations. First, measuring glucose at 2 h after a meal may not be ideal, as variation in diet 2 could change PPG by more than 20 mg/dL, 13 and variation in blood collection time (2 ± 0.5 h in practice 12 ) could introduce bias as PPG could be time-sensitive around 2 h. 13 Second, the use of antidiabetic medications could produce bias, as these medications affect PPG.…”
Section: Introductionmentioning
confidence: 99%
“…HOMA-IR is relatively inexpensive since it is derived from measurement of glucose and insulin in a fasting blood sample. Despite its convenience, HOMA-IR is widely regarded to have significant limitations (Pisprasert et al 2013 ; Wallace et al 2004 ; Thompson et al 2014 ) and can even lead to different conclusions compared to other insulin resistance measures (Reaven 2013 ). Broadly speaking, it is widely accepted that methods such as the hyperinsulinemic-euglycemic clamp (Defronzo 1979 ) or the frequently sampled intravenous glucose tolerance test [FSIGT; (Bergman 1989 )] are more desirable.…”
Section: Introductionmentioning
confidence: 99%